LABOR MANAGEMENT COMMITTEE [Philip Morris Memo] - SCRUGGS,JF (Tufts Archival Research Center, 2007)
Memorandum from John F. Scruggs of Philip Morris discussing reconstitution of Labor Management Committee (LMC). Discusses terms of agreement between and concessions by labor and companies. Identifies leadership of LMC and new legal framework for LMC.